2003
DOI: 10.1210/jc.2002-021592
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Thyroid Hormone Pathway Genes Are Associated with Plasma TSH and Iodothyronine Levels in Healthy Subjects

Abstract: Single nucleotide polymorphisms (SNPs) in genes involved in thyroid hormone metabolism may affect thyroid hormone bioactivity. We investigated the occurrence and possible effects of SNPs in the deiodinases (D1-D3), the TSH receptor (TSHR), and the T(3) receptor beta (TR beta) genes. SNPs were identified in public databases or by sequencing of genomic DNA from 15 randomly selected subjects (30 alleles). Genotypes for the identified SNPs were determined in 156 healthy blood donors and related to plasma T(4), fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
199
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(231 citation statements)
references
References 35 publications
30
199
2
Order By: Relevance
“…In addition, this SNP is associated with higher serum TSH but not thyroid hormone levels in healthy individuals (128) and with lower T3 release after TRH infusion (129). However, this change was not correlated with differences in general well-being, cognitive function or the response to therapy with T3+T4 in hypothyroid patients in same study, but not in others (130,131).…”
Section: Gene Polymorphismsmentioning
confidence: 69%
“…In addition, this SNP is associated with higher serum TSH but not thyroid hormone levels in healthy individuals (128) and with lower T3 release after TRH infusion (129). However, this change was not correlated with differences in general well-being, cognitive function or the response to therapy with T3+T4 in hypothyroid patients in same study, but not in others (130,131).…”
Section: Gene Polymorphismsmentioning
confidence: 69%
“…In this context it is interesting that a recently identified polymorphism in the gene coding for the type two deiodinase, the enzyme responsible for the regulation of T 3 availability to the tissues, has been proposed in order to help identifying subgroups more likely to benefit from T 4 /T 3 combination therapy (23). Another polymorphism, located in OATP1C1, a thyroid hormone transporter expressed at the blood-brain barrier, has been associated with fatigue and depression (24).…”
Section: Discussionmentioning
confidence: 99%
“…The causative genes are, however, not well established. Well-known TH pathway genes such as the deiodinases (8)(9)(10)(11)(12), TSH receptor (10,13,14) and TH transporters (15)(16)(17) have been associated with TH serum levels, but their contribution to the overall variation is modest (12,13). A genome-wide linkage scan by Panicker et al (18) identified eight chromosomal loci involved in the control of the pituitarythyroid axis, but as can be expected from this type of study, the actual genes were not identified.…”
Section: Introductionmentioning
confidence: 97%